Lewy Body-Associated Proteins A-Synuclein (a-syn) as a Plasma-Based Biomarker for Parkinson’s Disease - Zhao, Xuemiao; He, Haijun; Xiong, Xi; Ye, Qianqian; Feng, Feifei; Zhou, Shuoting; Chen, Weian; Xia, Kai; Qian, Shuangjie; Yang, Yunjun; Xie, Chenglong (Frontiers in Aging Neuroscience, 2022)
Introduction To explore the combined diagnostic value of plasma Lewy body-associated proteins (p-Asyn at ser129, total α-syn, and oligomeric α-syn) for the diagnosis of PD versus healthy controls (HCs) and other PD syndromes (PDs), as well as clinical characteristics prediction. Methods This study included 145 participants: 79 patients with PD, 24 patients with PDs, and 42 HCs. A panel of plasma levels of p-Asyn, total α-syn, and oligomeric α-syn was measured by enzyme-linked immunosorbent assay (ELISA). The primary outcome was the discriminative accuracy of the combined three plasma biomarkers for PD. Results The mean age was 65.43 (SD, 7.467) in the control group, 64.49 (SD, 8.224) in participants with PD, and 69.25 (SD, 7.952) in PDs. The plasma Lewy body-associated protein levels were significantly higher in patients with PD than in age-matched HCs, However, there was no difference in patients with PD and PDs. Of note, a combination of plasma p-Asyn, total α-syn, and oligomeric α-syn was a better biomarker for discriminating PD from HCs, with an AUC of 0.8552 (p < 0.0001, 95%CI, 0.7635–0.9409), which was significantly higher than plasma p-Asyn (ΔAUC, 0.1797), total α-syn (ΔAUC, 0.0891) and oligomeric α-syn (ΔAUC, 0.1592) alone. Meanwhile, Lewy body-associated proteins had no connections between different motor stages and dementia performances. Conclusion Our results suggested that plasma Lewy body-associated proteins, may serve as a non-invasive biomarker to aid the diagnosis of PD from HCs. In addition, increased plasma Lewy body-associated proteins were not associated with the progression of motor and non-motor symptoms.